ARTICULATING TAKFIR: Ayman Al-Zawahiri and The Global Jihad Ideology - Asrori, Saifudin; Bakhtiar, Amsal (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Takfir is an ideology of excommunicating fellow Muslims because of having different beliefs or expressing a different point of view. This article deals with the development of the takfir doctrine which separates some groups not only based on theological aspects but also on socio-political aspects, such as justifying the democratic system or collaborating with enemies of Islam. It particularly addresses the question of how Ayman al-Zawahiri globalized the takfir doctrine as a campaign against secularism, capitalism, human rights, and environmental crisis, in order to invite local jihadist groups to fight together in a global sphere.